Circulating Plasma MicroRNA-208a as Potential Biomarker of Chronic Indeterminate Phase of Chagas Disease - Linhares-Lacerda, Leandra; Granato, Alessandra; Gomes-Neto, João Francisco; Conde, Luciana; Freire-de-Lima, Leonardo; de Freitas, Elisangela O.; Freire-de-Lima, Celio G.; Coutinho Barroso, Shana P.; Jorge de Alcântara Guerra, Rodrigo; Pedrosa, Roberto C.; Savino, Wilson; Morrot, Alexandre (Frontiers in Microbiology, 2018)
Chagas cardiomyopathy is the most severe clinical manifestation of chronic Chagas disease. The disease affects most of the Latin American countries, being considered one of the leading causes of morbidity and death in the continent. The pathogenesis of Chagas cardiomyopathy is very complex, with mechanisms involving parasite-dependent cytopathy, immune-mediated myocardial damage and neurogenic disturbances. These pathological changes eventually result in cardiac myocyte hypertrophy, arrhythmias, congestive heart failure and stroke during chronic infection phase. Herein, we show that miR-208a, a microRNA that is a key factor in promoting cardiovascular dysfunction during cardiac hypertrophy processes of heart failure, has its circulating levels increased during chronic indeterminate phase when compared to cardiac clinical forms in patients with Chagas disease. In contrast, we have not found altered serum levels of miR-34a, a microRNA known to promote pro-apoptotic role in myocardial infarction during degenerative process of cardiac injuries thus indicating intrinsic differences in the nature of the mechanisms underlying the heart failure triggered by Trypanosoma cruzi infection. Our findings support that the chronic indeterminate phase is a progressive phase involved in the genesis of chagasic cardiopathy and point out the use of plasma levels of miR-208a as candidate biomarker to be udes in risk-prediction score for patients in clinical prognosis.